2006
DOI: 10.1016/j.coph.2006.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme 2 in lung diseases

Abstract: The renin-angiotensin system (RAS) plays a key role in maintaining blood pressure homeostasis, as well as fluid and salt balance. Angiotensin II, a key effector peptide of the system, causes vasoconstriction and exerts multiple biological functions. Angiotensin-converting enzyme (ACE) plays a central role in generating angiotensin II from angiotensin I, and capillary blood vessels in the lung are one of the major sites of ACE expression and angiotensin II production in the human body. The RAS has been implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
361
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(377 citation statements)
references
References 61 publications
9
361
0
7
Order By: Relevance
“…18,19 Angiotensin II generated by ACE promotes lung injury and conversion of fibroblasts into myofibroblasts followed by the accumulation of collagen. 28,29 Epithelioid cells in lung granulomas of ApoE Ϫ/Ϫ mice have shown strong ACE immunoreactivity that, similar to human granulomas, may contribute to the development of fibrotic changes in lungs.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Angiotensin II generated by ACE promotes lung injury and conversion of fibroblasts into myofibroblasts followed by the accumulation of collagen. 28,29 Epithelioid cells in lung granulomas of ApoE Ϫ/Ϫ mice have shown strong ACE immunoreactivity that, similar to human granulomas, may contribute to the development of fibrotic changes in lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the level of AngII can be seen up to the expression level of ACE2 (20). It is thought that the activation of the ACE2 pathway also provides protection against several lung diseases besides the inhibition of the ACE pathway (3). To the best of our knowledge, ACE2 and its product Ang1-7 as counter balanced components of RAS are not defined in asthma, although other RAS components are widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…It targets several tissues such as the brain, pituitary gland, heart, blood vessels, liver, kidneys, and adrenal glands (1,2). RAS includes different enzymes that have critical importance in the pathophysiological processes of several diseases (3,4). Renin is the key enzyme of RAS and converts inactive angiotensinogen (AGT) to angiotensinI (AngI) (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Studies demonstrated that ACE2 and ANG-(1-7) may exert protective effects in kinds of lung diseases, 4,5,14) which effects during the progression of PF were being intensively investigated.…”
mentioning
confidence: 99%